Improved Charge Separation and Injection Efficiencies of Bismuth Vanadate Photoanode by Depositing Composite CoOx/CuO Cocatalyst. Issue 30 (10th August 2022) - Hu, Yingfei; Hu, Qingyuan; Zhong, Qian; Guan, Hangmin; Hao, Lingyun; Wang, Yuanyuan; Zhang, Wenyan; Du, Hongxiu; Tian, Wenjie
Abstract: Exploring cheap and efficient cocatalysts is particularly important for a photoanode during photoelectrochemical (PEC) water splitting. Herein, we demonstrate that composite CoOx /CuO cocatalyst could efficiently enhance the oxygen evolution activity of BiVO4 . The onset potential of BiVO4 shifts negatively from 0.42 to 0.38 V vs. the reversible hydrogen electrode (RHE), and the photocurrent of BiVO4 increases from 0.42 mA cm −2 to 1.58 mA cm −2 at 1.23 V vs. RHE, which increases by about 3.76 times. It was confirmed by subsequent electrochemical and physical characterization that the charge separation and injection efficiency were improved, and the IPCE was also improved. Systematic studies indicate that composite CoOx /CuO cocatalyst exhibits better performance than the single CoOx or CuO cocatalyst for promoting the separation of electron‐hole, and accelerating the surface water oxidation reaction. Abstract : A composite CoOx /CuO cocatalyst was deposited on BiVO4, greatly improving the PEC performance for water oxidation. Both the charge separation and the surface water oxidation reaction were significantly enhanced.